A PSYCHOLOGICAL ANALYSIS OF THE MAIN CHARACTERS IN MOVIE “PENYALIN CAHAYA” - Melissha Enintha Hutajulu; Rina Octavia Simarmata; Harpen H. P. Silitonga (Jurnal Scientia, 2023)
This study aims to determine (1) the types of psychological analysis used in the main characters of the movie Penyalin Cahaya. (2) the most dominant type of psychological analysis of the five types of psychological analysis contained in the movie Penyalin Cahaya. This research is to find out the types of psychological analysis as part of psycholinguistics. Here the focus of the study is psychological analysis. This study used descriptive qualitative as approach and research design is an documentation analysis to describe and explain the characteristics or qualities of a phenomenon or subject. The data source in this research is the script of the movie Penyalin Cahaya by Wregas Bhanuteja. This research is based on Sigmund Freud in all update theories. The data analysis carried out in this research was in the form of classifying of data and describing data one by one in a table. The researcher found that there were five types of psychological analysis used in Penyalin Cahaya movie by Wregas Bhanuteja and of the five types of psychological analysis there are 192 data in the movie Penyalin Cahaya. From the total 192 data, there are 61 sentences of analysis data, 8 frequencies of Psychometric testing with percentage (13,1%), 6 frequencies of Projective tests with percentage (9,8%), 16 frequencies of Behavioral observation with percentage (26,2%), 14 frequencies of Psychoanalytic analysis with percentage (22,9%), and 17 frequencies of Humanistic analysis with percentage (27,8%). So, of five the types psychological analysis in the movie “Penyalin Cahaya” it shows that the movie mostly dominant used the Humanistic analysis with 17 frequency and percentage (27,8%).